2023
DOI: 10.2106/jbjs.22.01374
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management with Functional Brace Versus Various Surgical Fixation Techniques for Humeral Shaft Fractures

Abstract: Background: Historically, humeral shaft fractures have been successfully treated with nonoperative management and functional bracing; however, various surgical options are also available. In the present study, we compared the outcomes of nonoperative versus operative interventions for the treatment of extra-articular humeral shaft fractures.Methods: This study was a network meta-analysis of prospective randomized controlled trials (RCTs) in which functional bracing was compared with surgical techniques (includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Humeral shaft fractures have historically been predominantly treated nonoperatively, but recent studies have suggested that nonunion rates are much higher than previously reported. A meta-analysis of 21 RCTs compared functional bracing with various operative fixation techniques 6 . Bracing had a significantly higher rate of nonunion (17.4%) than open reduction and internal fixation (ORIF) (5.2%), minimally invasive plate osteosynthesis (0.6%), and antegrade nailing (6.1%).…”
Section: Humeral Shaft and Elbowmentioning
confidence: 99%
“…Humeral shaft fractures have historically been predominantly treated nonoperatively, but recent studies have suggested that nonunion rates are much higher than previously reported. A meta-analysis of 21 RCTs compared functional bracing with various operative fixation techniques 6 . Bracing had a significantly higher rate of nonunion (17.4%) than open reduction and internal fixation (ORIF) (5.2%), minimally invasive plate osteosynthesis (0.6%), and antegrade nailing (6.1%).…”
Section: Humeral Shaft and Elbowmentioning
confidence: 99%